Natural compound-derived epigenetic regulators targeting epigenetic readers, writers and erasers - Yuqing Yang, Anne; Kim, Hyuck; Li, Wenji; Tony Kong, Ah-Ng (Current Topics in Medicinal Chemistry, 2016)
Post-translational modifications can affect gene expression in a long-term manner without changes in the primary nucleotide sequence of the DNA. These epigenetic alterations involve dynamic processes that occur in histones, chromatin-associated proteins and DNA. In response to environmental stimuli, abnormal epigenetic alterations cause disorders in the cell cycle, apoptosis and other cellular processes and thus contribute to the incidence of diverse diseases, including cancers. In this review, we will summarize recent studies focusing on certain epigenetic readers, writers, and erasers associated with cancer development and how newly discovered natural compounds and their derivatives could interact with these targets. These advances provide insights into epigenetic alterations in cancers and the potential utility of these alterations as therapeutic targets for the future development of chemopreventive and chemotherapeutic drugs.
Keywords: Readers